Modification Strategies of Copper Molybdate-based Photocatalysts for Degradation of Organic Compounds in Wastewater: A Mini Review - Hamidah binti Abdullah; Rohayu binti Jusoh; Wahaizad bin Safie; Ricca Rahman binti Nasaruddin; Maksudur Rahman Khan; Md Noor bin Arifin (Bulletin of Chemical Reaction Engineering & Catalysis, 2026)
Visible-light photocatalysis has emerged as a sustainable tertiary‐treatment option. Within this arena, copper molybdate (CuMoO4) is attractive because of its narrow bandgap enables direct solar harvesting while relying on earth-abundant elements. Yet pristine CuMoO4 suffers from low surface area (< 10 m2/g), rapid electron-hole recombination and Cu2+ photocorrosion, which curb quantum yields and raise secondary-pollution concerns. This mini review critically synthesizes research published between 2019 and 2025 on strategies devised to surmount these limitations. Four major areas are surveyed: (i) morphology engineering that multiplies active-site density and deepens light scattering; (ii) plasmonic or single-atom noble-metal decoration that extends spectral response and accelerates interfacial charge separation via localized surface plasmon resonance; (iii) band-gap and defect modulation through doping or oxygen-vacancy creation, narrowing band gap and introducing long-lived trapping states, and (iv) construction of p-n heterojunctions (e.g., ZnO/CuMoO4, graphitic carbon nitride/copper molybdate (g-C3N4/CuMoO4) that yield order-of-magnitude rate enhancements by spatially separating redox half-reactions. The synthesis approaches, from hydrothermal and co-precipitation to thermal-decomposition and solid-state reactions directly influence crystallinity, morphology and defect chemistry, with optimal hydrothermal conditions (180 oC, 10 h) producing high-purity α-CuMoO4 microspheres and oxygen-vacancy-rich Cu-rich phases delivering up to a 0.5 eV bandgap reduction. Emphasis is placed on correlating structural descriptors with pollutant-mineralization kinetics and on emerging green-synthesis trends. Remaining challenges and research priorities including stability against Cu leaching, scalable fabrication and in-situ mechanistic probes are highlighted to guide future catalyst design. Copyright © 2026 by Authors, Published by BCREC Publishing Group. This is an open access article under the CC BY-SA License (https://creativecommons.org/licenses/by-sa/4.0).